2019
DOI: 10.1089/neu.2018.6009
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Initial Validation of Clinical Phenotypes of Children Presenting with Concussion Acutely in the Emergency Department: Latent Class Analysis of a Multi-Center, Prospective Cohort, Observational Study

Abstract: The identification of clinical phenotypes may help parse the substantial heterogeneity that characterizes children with concussion. This study used latent class analysis (LCA) to identify discernible phenotypes among children with acute concussion and examine the association between phenotypes and persistent post-concussive symptoms (PPCS) at 4 and 12 weeks post-injury. We conducted LCA of variables representing pre-injury history, clinical presentation, and parent symptom ratings, derived from a prospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…Few recent studies have parsed heterogeneity in concussion symptoms using clustering analyses. 10-12 The reported subgroups differed from those found in the present study. Differences between symptom profiles arose because our multi-symptom features are associated with brain structure and not driven by variability in symptoms alone.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Few recent studies have parsed heterogeneity in concussion symptoms using clustering analyses. 10-12 The reported subgroups differed from those found in the present study. Differences between symptom profiles arose because our multi-symptom features are associated with brain structure and not driven by variability in symptoms alone.…”
Section: Discussioncontrasting
confidence: 99%
“…To remedy this shortcoming, a growing number of studies aimed to parse the clinical heterogeneity in concussions by algorithmically partitioning patients into discrete subgroups based on symptoms. 10-12 Other studies aim instead to account for heterogeneity in white matter structure alterations. 13-15 Ware et al 15 built individualized maps of white matter abnormalities which revealed substantial inter-subject variability in traumatic axonal injury and minimal consistency of subject-level effects.…”
Section: Introductionmentioning
confidence: 99%
“…Around 12% of children sustaining a mTBI have PPCS three months following injury 5 . There are several PPCS phenotypes with the commonest symptoms being headaches, fatigue, sleep disturbances and cognitive difficulties 6 . These symptoms have a detrimental impact on health-related quality of life and long-term outcomes [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Historically, psychometric analyses of various symptom scales identified four subdomains of concussion symptoms: physical, cognitive, emotional and sleep/fatigue [9][10][11]. Recent studies support that mTBIs are heterogeneous in clinical presentation across domains, resulting in thematic phenotypes that allow for subtype-targeted management [12][13][14][15][16]. A US Department of Defense-tasked expert workgroup classified postconcussive symptoms and defined nonmutually exclusive clinically relevant subtypes including: vestibular; ocular-motor; anxiety/mood; cognitive; and headache/migraine [15,17,18].…”
mentioning
confidence: 99%